PERANCANGAN SISTEM E-SURAT BERBASIS WEB DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PALEMBANG - M Abdul Rahman; Gina Agiyani (Yayasan Nuraini Ibrahim Mandiri, 2025)
The rapid development of information technology has driven the digitization of government administration, including the management of correspondence, which is still carried out manually at the Palembang City Library and Archives Office. This manual system causes various problems such as inefficient recording, difficulty in searching for archives, and the risk of document loss. This study aims to design and implement a web-based e-mail system to enhance the efficiency and effectiveness of incoming and outgoing mail management. The method used is the Waterfall model, which includes the following stages: needs analysis, system design, coding, testing, and implementation. System modeling employs the Unified Modeling Language (UML), encompassing use case diagrams and activity diagrams. The results of the study indicate that the e-mail system can accelerate the process of recording and searching for documents digitally, as well as reduce dependence on physical archives. This system is expected to provide a solution to the problems of accumulated mail and the potential loss of documents within the institution.